2016
DOI: 10.1017/s003118201500181x
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular and comparative morphological analysis of central European parasitic flatworms of the superfamily Brachylaimoidea Allison, 1943 (Trematoda: Plagiorchiida)

Abstract: The Brachylaimoidea are digenean parasites of vertebrates, including humans, domestic animals, poultry and wild game. Numerous Brachylaimoidea, particularly adults of Brachylaima and Leucochloridium, are difficult to identify to species. We provide and analyse sequences of two nuclear (18S rDNA, ITS2) and two mitochondrial (CO1, ND1) DNA loci of central European species of the Brachylaimoidea, namely Leucochloridium holostomum, Leucochloridium paradoxum, Leucochloridium perturbatum, Leucochloridium subtilis, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…These studies have resulted in more stable classification schemes of genera within families and families within superfamilies of the subclass Digenea. For example, at the superfamily level, the studies of Microphalloidea (Tkach et al, 2003), Lepocreadioidea Odhner, 1905(Bray et al 2009, Brachylaimoidea (Heneberg et al, 2016) Echinostomatoidea Looss, 1899 (Tkach et al, 2016), and the recent study of Hemiuroidea by Sokolov et al (2018), can be highlighted. Additionally, at the family level, several studies have determined the inter-relationships among genera and the re-organization of subfamilies, such as the study by Tkach et al (2001) with Omphalometridae Looss, 1899 by Choudhury et al (2007) Atopkin et al (2019) with Haploporidae.…”
Section: Journal Of Helminthology 271mentioning
confidence: 99%
“…These studies have resulted in more stable classification schemes of genera within families and families within superfamilies of the subclass Digenea. For example, at the superfamily level, the studies of Microphalloidea (Tkach et al, 2003), Lepocreadioidea Odhner, 1905(Bray et al 2009, Brachylaimoidea (Heneberg et al, 2016) Echinostomatoidea Looss, 1899 (Tkach et al, 2016), and the recent study of Hemiuroidea by Sokolov et al (2018), can be highlighted. Additionally, at the family level, several studies have determined the inter-relationships among genera and the re-organization of subfamilies, such as the study by Tkach et al (2001) with Omphalometridae Looss, 1899 by Choudhury et al (2007) Atopkin et al (2019) with Haploporidae.…”
Section: Journal Of Helminthology 271mentioning
confidence: 99%
“…The superfamily Brachylaimoidea has potential veterinary importance and complex taxonomic history. Currently, the superfamily Brachylaimoidea contains at least 20 valid species that consist of parasites of mammals and birds (Heneberg et al, 2016). Despite their importance, no mt genome had been sequenced and characterized for any members of the superfamily Brachylaimoidea.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic relationships of brachylaimids were inferred by sequences of 28S rDNA and cox1, using an unknown species found in this study and related taxa published in DNA databases [29,30,31,32]. The NJ phylogenetic trees of the two genes strongly suggested that the unknown species belongs to the genus Brachylaima, although the number of taxa available for the tree construction was insufficient ( Supplementary Fig.…”
Section: Dna Phylogeny and Diversitymentioning
confidence: 85%